x-3(9+x)=-11

Simple and best practice solution for x-3(9+x)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3(9+x)=-11 equation:


Simplifying
x + -3(9 + x) = -11
x + (9 * -3 + x * -3) = -11
x + (-27 + -3x) = -11

Reorder the terms:
-27 + x + -3x = -11

Combine like terms: x + -3x = -2x
-27 + -2x = -11

Solving
-27 + -2x = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + -2x = -11 + 27

Combine like terms: -27 + 27 = 0
0 + -2x = -11 + 27
-2x = -11 + 27

Combine like terms: -11 + 27 = 16
-2x = 16

Divide each side by '-2'.
x = -8

Simplifying
x = -8

See similar equations:

| x-3(9+x)=-11 | | 2(2x+3)-4(2-3x)=6+x | | 14-2(3p+p)=6(4+p) | | 5(2x+8)=7x+20 | | 0.05x+0.04y=420 | | -7-2x=-19 | | -1(3z+4)=6z+-3(3z+2) | | 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= | | 5c+4c= | | 3(2x+5)-x=11 | | 5c+4n= | | [x-3]=12 | | z+30=16 | | 14+3n=8n-3(1n-4) | | 17=2x+3 | | 4(2x+1)=x+4 | | 18-10(x-1)=4x | | 2-4/2 | | 1/3(5y-1) | | 8+f(4/5)=0 | | -8x-(3x+6)=4-1x | | 5x-4=1-x | | (y^2-4y+3)/(5y^2-40y+35) | | 4y-3(2y-7)=5y+12 | | v^2-v=30 | | x-5+3x/4=-5+7x/4 | | x+2-8=14 | | 28+a+(-48.08)*(1.414213562)=0 | | 2t+3=-12 | | 34+a+(-48.08)*(1.414213562)=0 |

Equations solver categories